IMPLEMENTASI SISTEM PEMIDANAAN DUA JALUR (DOUBLE TRACK SYSTEM) BAGI PELAKU PENYALAHGUNA NARKOTIKA - Fransilirus Nong Richi (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
The main discussion of this study is related to the application of punishment for narcotics abusers who are considered inappropriate. The main problem in this research is related to the implementation of the double track system as an effort to reduce overcrowding in Correctional Institutions, as well as to analyze the considerations of the panel of judges who tend to ignore the double track system and prefer to apply sanctions. imprisonment, as in the Decision of the Tanjung Balai Karimun District Court Number: 119/Pid.Sus/2021/PN Tbk and the Metro District Court Decision Number: 70/Pid.Sus/2021/PN Met. This research method is included in the form of normative juridical research which originates from secondary data and is supported by primary data. The results of this study conclude that placing narcotics abusers in Correctional Institutions actually exacerbates overcrowding which has now reached 109% (one hundred and nine percent). This is what then needs to build a paradigm of stopping criminalization or by decriminalizing narcotics abusers. The concept of decriminalization in question is by implementing a double track system of punishment, as another form of sanction apart from criminal sanctions, such as Portugal and Thailand which have previously implemented this criminal system and have proven successful in reducing overcrowding. This is what then needs to build a paradigm of stopping criminalization or by decriminalizing narcotics abusers. The concept of decriminalization in question is by implementing a double track system of punishment, as another form of sanction apart from criminal sanctions, such as Portugal and Thailand which have previously implemented this criminal system and have proven successful in reducing overcrowding. This is what then needs to build a paradigm of stopping criminalization or by decriminalizing narcotics abusers.